PENGARUH PROGRAM P5 TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA DI ERA KURIKULUM MERDEKA PADA SISWA SEKOLAH DASAR - Sintia Bona; Siprianus Jewarut (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study evaluates the effectiveness of the Pancasila Student Profile (P5) program focusing on the Critical Thinking dimension, implemented for fourth-grade students at SD Negeri 01 Bengkayang. Using a qualitative approach, the research employs observation, interviews, and documentation as primary data collection methods. The findings reveal that the P5 program significantly improved students' critical thinking skills, including problem identification, information analysis, and creative solution formulation. Project-based activities provided opportunities for collaboration, critical thinking, and confidence in presenting ideas. Additionally, students exhibited progress in logical argumentation and reflection on their learning processes. However, challenges such as limited time and diverse student capabilities emerged. Teachers play a vital role as facilitators in fostering an active and inclusive learning environment. Adaptive teaching strategies, such as ability-based group divisions, have proven effective in addressing these obstacles. The study concludes that P5 has substantial potential to enhance students’ critical thinking skills sustainably, preparing them for 21st-century educational demands. It recommends further integration of project-based approaches into the curriculum to optimize learning outcomes and foster holistic development